Language policy and the academic excellence evaluation - Nečak Lük, Albina (Anali PAZU HD, 2022)
The question of language choice and language use with university pedagogical activities as well as with publication of the scientific research outcomes has been a permanent issue in the debate on evaluation of academic excellence and the related status of the university teachers in Slovenia. Formal support to publishing of scientific reports in a foreign, usually English language which is promoted as a mark of quality of the scientific production (in the system of evaluation of the national research agency) has been disputed on several occasions. In view of the emerging internationalisation of the university sphere, some possible consequences of an inadequately formulated language policy as well as reasons for creation of an expedient relationshps between Slovene and English as languages of high/higher education and scientific dissemination, have been discussed in this study.